2019
DOI: 10.1002/cssc.201901309
|View full text |Cite
|
Sign up to set email alerts
|

Nitride‐Derived Copper Modified with Indium as a Selective and Highly Stable Catalyst for the Electroreduction of Carbon Dioxide

Abstract: The lack of efficient catalysts prevents the electrocatalytic reduction of carbon dioxide from contributing to the pressing target of a carbon‐neutral economy. Indium‐modified copper nitride was identified as a stable electrocatalyst selective toward CO. In2O3/Cu3N showed a Faradaic efficiency of 80 % at 0.5 V overpotential for at least 50 h, in stark contrast to the very limited stability of the benchmark In2O3/Cu2O. Microfabricated systems allowed to correlate activity with highly stable interfaces in indium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…(f) Evolution of the elemental distribution of indium obtained by SEM‐EDXS at different reaction times in microfabricated electrodes. Reproduced with permission [100] . Copyright 2019, Wiley.…”
Section: Bimetallic Indium‐based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…(f) Evolution of the elemental distribution of indium obtained by SEM‐EDXS at different reaction times in microfabricated electrodes. Reproduced with permission [100] . Copyright 2019, Wiley.…”
Section: Bimetallic Indium‐based Catalystsmentioning
confidence: 99%
“…They further designed an ultra-stable In 2 O 3 /Cu N catalyst that maintained a FE CO of 80 % at À 0.6 V vs. RHE in KHCO 3 (0.1 M) for at least 50 h (Figure 8e). [100] The excellent stability was attributed to the formation of metastable N species that greatly suppressed the diffusion of indium species and hence prevented the CuÀ In interfaces from being vanished (Figure 8f).…”
Section: Cu-inmentioning
confidence: 99%
“…The relatively low selectivity to products involving more than two carbon atoms, in particular C 3 products (allyl alcohol and n-propanol), also remains an issue for virtually all Cu-based catalysts. 16,[23][24][25] Although surface roughening has contributed to the selective formation of multi-carbon products on Cu, there remains a need for novel ways to produce Cu surfaces with a more controlled roughness in order 3 to clearly investigate the structure-activity relationship of CO 2 RR performances.…”
Section: Introductionmentioning
confidence: 99%
“…Microfabrication can contribute to this need of describing selectivity patterns in terms of chemical environment descriptors by providing catalysts with controlled geometry. This set of techniques has been demonstrated through lithographic approaches to gather insights into the formation and nature of active sites in multicomponent systems 31,32 and into the operation of bifunctional catalysts. 33 In this study we identified ultra-short pulsed (USP, pulse duration from fs to ps) laser ablation 34,35 as the technique of choice for the development of model copper electrodes.…”
Section: Introductionmentioning
confidence: 99%